Explaining compelling similarities in Macedonian and Montenegrin dialects: Perfects and adjectival participles - Curtis, Matthew C. (Zeitschrift für Balkanologie, 2010)
The present study follows up on an article by ROBERT GREENBERG (2000) who observed a number of phonological, morphological and syntactic similarities between Southwest Montenegrin and Southwest Macedonian dialects. These similarities include a distinction between a ‘light’ and ‘dark’ lateral, a voiced dental affricate, preservation of case forms, similarities in vocative forms, reduplication of object pronouns, use of simple preterites (aorist and imperfect) and a perfect formed from with the auxiliary from the verb ‘to have.’ In this paper, I take the suggestion given by Greenberg himself that northern Albanian (Geg) dialects should be explored as a possible cause for these similarities. To this I use FRANS VAN COETSEM’s (1988/2000) framework for language contact, to see if bilingualism between Albanian and Slavic languages is likely to have produced the results that Greenberg observed. Although similarities with Albanian exist for each of the given features, there are many possible causes of the dialects’ characteristics. Thus I take a more in-depth look at one particular similarity: a perfect formed by the verb ‘to have’ plus participle. Looking at dialects form Montenegro, Macedonia and Kosovo for Slavic and Kosovo and Albania for Albanian, this paper details the forms of perfects in three Slavic and three Albanian dialects to compare the similarities between the neighboring languages. The evidence suggests that although Albanian may be responsible for some of the similarities, it is by no means the complete solution to understanding these similarities, and in fact, Albanian dialects may, perhaps, show some influence of Slavic in perfect constructions – in allowing constructions with a ‘to be’ auxiliary. Although no complete answer is given to why these compelling similarities exist, this study argues that there are likely several causes for these similarities and that no single answer satisfactorily explains all of the features. Contact with Albanian, however, remains an important part of how these intriguing Slavic dialects have developed.